A retrospective review of measles outbreaks in Ibb Governorate, Yemen (2020–2023) - Wadee Abdullah Al-Shehari; Wadhah Hassan Edrees; Eglal Ahmed Qasem; Yahya Ali Al-Qadhi; Abdulrahman Abdullah Humaid; Ali Ahmed Al-Halani (Tropical Medicine and Health)
Abstract Background Measles, a highly infectious disease that can lead to serious health problems and even death, has recently recurred worldwide despite the measures taken, with Yemen experiencing the most outbreaks among countries worldwide. There is a scarcity of current information regarding the measles epidemic in the Ibb Governorate of Yemen. Consequently, this retrospective analysis aimed to ascertain the pattern of measles outbreaks in Ibb Governorate, Yemen, during the 4-year period from 2020 to 2023. Methods The secondary measles data contained in the database of the Health and Environment Office at Ibb Governorate between 2020 and 2023 were used for this retrospective analysis. Results Of the 3,898 suspected measles cases, the majority of cases were recorded among males (53.2%), in the 0–4 age group (65.5%), in autumn (31.6%), and in 2023 (52.5%). The cumulative incidence rate of measles cases was 12.6 cases per 10,000 population, with the highest rates in males (13.7 cases) and the age group of 0–4 years (57.9 cases). The incidence rate has been increasing between 2020 and 2023, from 0.7 to 6.8 cases per 10,000 people. Furthermore, the overall fatality rate for measles cases was 0.87% and was significantly higher in children aged 0–4 years. The districts of As Saddah (44.7 cases) and Yarim (30.6 cases) recorded the highest incidences of measles. Most of the people who had measles had a rash (3,898; 100%), fever (3,887; 99.7%), cough (3,269; 83.9%), and runny nose (2,763; 70.9%). Additionally, 60.8% (2,370) of the cases were among unvaccinated individuals. Conclusion Current findings indicate that measles cases are increasing over the years and could pose a significant threat to the population if left unaddressed. A stronger vaccination program, better healthcare infrastructure, the fight against vaccine hesitancy, and international collaboration are crucial for controlling and eliminating measles in this country.